1993
DOI: 10.1172/jci116721
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-infected T lymphocytes in Epstein-Barr virus-associated hemophagocytic syndrome.

Abstract: The clonal composition of EBV-infected cells was examined in three cases of EBV-associated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(121 citation statements)
references
References 32 publications
3
115
0
3
Order By: Relevance
“…The majority of previous studies have reported single cases; however, the study by Quintanilla-Martinez et al described the clinicopathological features of 5 cases of this disease (2). In this study, we reviewed the clinicopatho- logical features of 17 cases with systemic EBV-positive T-cell LPD of childhood following acute EBV infection, including the present case (Table I) (2,(4)(5)(6)(7)(8)(9)(10)(11)(12). We revealed that clonal systemic proliferation of EBV-infected T-cells that appear morphologically innocuous with an activated cytotoxic phenotype expressing CD8 and/or CD4 is central to the disease.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of previous studies have reported single cases; however, the study by Quintanilla-Martinez et al described the clinicopathological features of 5 cases of this disease (2). In this study, we reviewed the clinicopatho- logical features of 17 cases with systemic EBV-positive T-cell LPD of childhood following acute EBV infection, including the present case (Table I) (2,(4)(5)(6)(7)(8)(9)(10)(11)(12). We revealed that clonal systemic proliferation of EBV-infected T-cells that appear morphologically innocuous with an activated cytotoxic phenotype expressing CD8 and/or CD4 is central to the disease.…”
Section: Discussionmentioning
confidence: 91%
“…In EBV-related hemophagocytic syndrome, it has been shown that viral-infected T cells release TNF-␣ and activate macrophages, resulting in massive hemophagocytosis. 28,29 These activated T cells might induce polyclonal B-cell activation through cytokine release and thereby induce high levels of IgG and EBV-related antibodies. On the other hand, it is unclear why HMB and high IgE were observed in patients with NK-cell type of CAEBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the viral status in the respective monocytic cell lines obtained may dictate the functional properties of the cells. Some human hemophagocytic syndromes are related to EBV infection (22,26,27). Related to the pathogenesis of this EBV-associated syndrome, enhanced phagocytosis and secretion of TNF-␣ by monocytes/macrophages (31, 40) seemingly result from an activation of their functions by EBV-infected T cells.…”
Section: Discussionmentioning
confidence: 99%